Inhibition of Gastric Emptying is Neither Necessary nor Sufficient for Peptide-Induced Satiety in the Rat - Conover, Kent (My University, 1988)
This research examines the hypothesis that the satiety effect of cholecystokinin octapeptide (CCK-8) is mediated by changes in gastric emptying. A method for collection of gastric emptying data, the double sampling procedure, is developed and validated for use in the rat. The double sampling technique permits repeated measurements of liquid gastric volume and thus describes the time course of emptying within a single experimental session. Further, the method allows determination of the amount of gastric secretion, volume emptied into the intestines, and amount of gastric load remaining in the stomach. Experiments are presented which: i) demonstrate the utility of the technique; ii) validate its accuracy in determining gastric volume; iii) indicate the stability of measurements obtained with this procedure; and iv) provide a procedure for quantitative evaluation of data obtained with this technique. Using the double sampling procedure, the ability of CCK-8 to delay gastric emptying and to influence feeding are then compared under similar experimental conditions. The effect of CCK-8 on gastric emptying is assessed in 6 hr deprived rats receiving 10 ml intragastric test loads of either .15M saline or 15% sucrose. Intraperitoneal (ip) injections of CCK-8 in doses of 1.4-22.4 ug/kg produce a dose-dependent retardation of gastric emptying of both saline and nutrient. Lower doses of CCK-8, 0.01 and 0.1 ug/kg, have no effect on gastric emptying. The effect of CCK-8 on feeding is assessed in rats tested under the same experimental conditions used in the gastric emptying studies. Doses of CCK-8 capable of retarding gastric emptying also suppress eating in a dose-dependent manner. These findings provide necessary correlational support for the hypothesis that satiety produced by CCK-8 is mediated by inhibition of gastric emptying. However, a further quantitative analysis of the correspondence of the gastric emptying and feeding effects of CCK-8 suggest that retardation of emptying may not account for the entire satiety effect of the peptide. The next set of studies provide direct tests of whether changes in gastric emptying mediate CCK-induced satiety. If gastric emptying plays a significant role in the satiety produced by CCK-8 then: i) the effects of CCK-8 on emptying and feeding should share similar kinetics, and ii) peptides that inhibit emptying should also inhibit feeding. I show that CCK-8 (5.6 ug/kg) injected coincident with introduction of an intragastric load or presentation of a test meal produces a rapid inhibition of both emptying and feeding. In contrast, the identical dose of CCK-8 administered 15 min before testing causes no inhibition of emptying, even though the peptide retains its ability to produce satiety. I also test the abilities of the peptides pentagastrin (100 ug/kg), bombesin (8 & 16 ug/kg) and secretin (2.86, 14.3 & 28.6 ug/kg) to reduce food intake and inhibit gastric emptying. Pentagastrin does not affect food intake or gastric emptying. Bombesin causes a small transient delay in emptying but a large and sustained suppression of eating. High dose secretin (14.3 ug/kg) causes no significant reduction of food intake, even though this dose of secretin inhibits emptying to the same degree as 1.4 ug/kg CCK-8, which does reduce intake. Thus, although CCK-8 does influence the rate of gastric emptying, the present results indicate that the inhibition of emptying by CCK is neither necessary nor sufficient to explain its satiety effect.
Relationship Between Gastric Emptying and CCK-8 Induced Satiety
Keywords: gastric emptying; rat; peptide-induced satiety; cck--8